A comparison of biomechanical parameters between two methods of countermovement jump - Akl, A.-R. (International Journal of Sports Science and Engineering, 2013)
The purpose of the present study was to compare of biomechanical parameters between countermovement jump with arm swing and countermovement jump no arm swing, and investigate the effect of arm swing to enhance the performance of countermovement jump. Five male high level athletes participated in this study were volleyball players (age: 20.2 ± 1.06 years; body mass: 82.77 ± 19.3 kg; height: 189.6 ± 9.34 cm). The two methods of countermovement jumps were performed on a strain gage force platform, high-speed motion capture system at a frequency of 250 Hz, video point v 2.5 2D motion analysis for kinematic parameters, and the integration was calculated by OriginPro 8.5 SR1 Data Analysis and Graphing Software. The following variables were analyzed: Maximum height, Low point, Height at TO, Maximum force, Velocity at TO, Kinetic Energy at TO, Potential Energy at TO, Impulse at TO, and the angles of lower limb at low point and take off. To examine the importance of biomechanical parameters on countermovement jump, a comparison between countermovement with arm swing and countermovement no arm swing and a correlations between arm swing and biomechanical parameters were used. The results showed, the performance (countermovement) was better among CMJ arm swing than CMJ no arm swing, of the parameters (Maximum height, Maximum force, Velocity at TO, Kinetic Energy at TO, Potential Energy at TO), and Arm swing was strongly correlated with Maximum force, Velocity at TO, Kinetic Energy at TO, Potential Energy at TO, and Knee angle at Low point. And Maximum height was strongly correlated with Height at TO, Maximum force, Velocity at TO, Kinetic Energy at TO, Potential Energy at TO and Impulse at TO. Finally, the percentage contribution arm swing in improving jump height was noted that arm swing led to an improvement in the CMJ arm swing by 27.08%.